COGNITIVE FLEXIBILITY DAN PROBLEM-FOCUSED COPING: KUNCI MENGATASI PROKRASTINASI AKADEMIK SISWA SMP - Nilam Puspasari, Dinda; Suhadianto, Suhadianto; Matulessy, Andik (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to analyse the role of Cognitive Flexibility and Problem-Focused Coping in relation to academic procrastination among junior high school students. Academic procrastination has often been associated with self-regulation, yet most studies have examined psychological factors separately. The simultaneous relationship between Cognitive Flexibility and Problem-Focused Coping remains underexplored, particularly among junior high school students in Indonesia. A quantitative correlational design was employed, involving 151 students from SMP Negeri 22 Surabaya selected through purposive sampling. Likert-scale questionnaires were used to measure the three main variables. Multiple linear regression analysis revealed that Cognitive Flexibility and Problem-Focused Coping jointly predicted academic procrastination significantly (F = 86.650; p < 0.001; R² = 0.539). Partially, Cognitive Flexibility showed a significant negative effect (B = -0.250; t = -2.313; p = 0.022), while Problem-Focused Coping demonstrated a stronger predictive contribution (B = -0.696; t = -6.763; p < 0.001).The theoretical contribution of this study lies in strengthening self-regulation models and highlighting the role of executive functions in adolescents’ academic behaviour, emphasizing that Cognitive Flexibility and adaptive coping strategies complement each other in reducing procrastination. The practical implication is that school-based interventions should prioritize active coping training, time management, and problem-solving skills. These findings can serve as the basis for psychological assistance and academic counselling programs to reduce procrastination tendencies among junior high school students. ABSTRAK Penelitian ini bertujuan menganalisis peran Cognitive Flexibility dan Problem-Focused Coping terhadap prokrastinasi akademik pada siswa SMP. Prokrastinasi akademik telah banyak dikaitkan dengan regulasi diri, tetapi sebagian besar penelitian hanya menyoroti salah satu faktor psikologis secara terpisah. Hubungan simultan antara Fleksibilitas Kognitif dan strategi coping berorientasi masalah masih jarang diteliti, khususnya pada populasi siswa SMP di Indonesia. Penelitian ini menggunakan pendekatan kuantitatif korelasional dengan melibatkan 151 siswa SMP Negeri 22 Surabaya yang dipilih melalui purposive sampling. Instrumen berupa skala Likert digunakan untuk mengukur ketiga variabel utama. Analisis regresi linier berganda menunjukkan bahwa Cognitive Flexibility dan Problem-Focused Coping secara simultan signifikan memprediksi prokrastinasi akademik (F = 86,650; p < 0,001; R² = 0,539). Secara parsial, Cognitive Flexibility berpengaruh negatif signifikan (B = -0,250; t = -2,313; p = 0,022), sementara Problem-Focused Coping memiliki kontribusi prediktif lebih besar (B = -0,696; t = -6,763; p < 0,001). Kontribusi teoretis penelitian ini adalah penguatan model regulasi diri dan fungsi eksekutif dalam perilaku akademik remaja, dengan menegaskan bahwa Fleksibilitas Kognitif dan strategi koping adaptif saling melengkapi dalam menekan prokrastinasi. Implikasi praktis penelitian ini menekankan perlunya intervensi berbasis sekolah yang berfokus pada pelatihan coping aktif, manajemen waktu, dan keterampilan pemecahan masalah, sehingga dapat digunakan sebagai dasar program pendampingan psikologis dan konseling akademik untuk mengurangi kecenderungan prokrastinasi siswa SMP.